WT1 as a substrate of HtrA2: a potential pathway for therapeutic targeting by HtrA proteases. (August 2010) - Chien, Jeremy
Evaluation of: Hartkamp J, Carpenter B, Roberts SGE: The Wilms' tumor suppressor protein wt1 is processed by the serine protease HtrA2/Omi. Mol. Cell 37, 159–171 (2010). WT1 is a transcription factor first cloned in 1990 as a tumor suppressor, and inactivating deletions and mutations in WT1 are found in childhood kidney Wilms' tumor. The tumor suppressive role of WT1 is further supported by in vitro and in vivo studies in which ectopic expression of WT1 attenuated cell growth and tumor formation by promoting apoptosis through induction of proapoptotic proteins. However, WT1 is also reported to be overexpressed in adult cancer, and the functional significance of overexpression or de novo expression of WT in adult cancers is not clear, although WT1 in adult cancer may represent isoform-specific differences in WT1 function. A paper by Hartkamp et al. is discussed in this article, reporting the identification of Wilms' tumor suppressor protein WT1 as a substrate of serine protease HtrA2 and the contribution of potential mechanistic insights into how distinct WT1 functions may be regulated through proteolysis by HtrA2.